The Effect of E-WOM and Brand Image on Purchasing Decisions of Automotive Products: Mediating Role of Brand Trust - Putri, Cindy Novtantia; Fauzi, Teddy Hikmat (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
The automotive industry, especially in the classification of four-wheeled vehicles, is one of the largest industries in Indonesia, which has massive and stable sales. In this sector, products from several global-scale automotive companies have long been the choice of Indonesian consumers, including Toyota as its leading brand. In this era of information technology, product marketing and communication has become embedded in digital forms and the internet along with the increasingly important role of social media. Electronic word of mouth (e-WOM) has been investigated to play an important role in establishing brand trust and purchases. This study attempts to analyze the effect of electronic word of mouth (e-WOM) and brand image on Toyota car purchasing decisions in Bandung by testing brand trust as a mediating variable. The research was conducted on Toyota consumers in Bandung who actively use Instagram social media. Sample collection was carried out using simple random sampling technique with data analysis using the PLS-SEM approach. The results show that E-WOM has a significant effect on brand trust (Path Coefficient=0.202; p-value= 0.033), and on purchasing decisions (Path Coefficient=0.226; p-value= 0.012). Empirical results show a significant effect of brand image on brand trust (Path Coefficient=0.526; p-value=0.000), and on purchasing decisions (Path Coefficient=0.210; p-value= 0.037). Direct analysis also shows a significant role of brand trust in purchasing decisions (Path Coefficient=0.460; p-value=0.000). Mediation analysis shows that brand trust is able to mediate the relationship between E-WOM on Purchase Decisions, and between Brand Image on Purchase Decisions. Keywords: brand image, brand trust, E-WOM, purchasing decision, toyota